Influence Of Non-Uniform Number Of Turns Per Coils And Stator Geometry On Unbalanced Magnetic Force In Brushless Permanent Magnet Machine - Abdullah Al Habshi, Syed Muhammad S (2016)
The Three Phase Permanent Magnet Brushless machines in which slot number and pole number combinations are similar such as differ by one have to be configured with asymmetric winding pattern in order to obtained perfect balanced back-emf among phases. However, the asymmetric winding pattern inherently results an unwanted force which is commonly known as an Unbalanced Magnetic Force or Unbalanced Magnetic Pull. An acoustic noise and vibration are the end results of this phenomenon. In some robotic application systems that require an accurate positioning control, this phenomenon is sometimes considerably severe. Investigations of electromagnetic performance in the asymmetric winding permanent magnet machines are carried out by using 2-D Finite-Element Analysis and the developed prototype machines are tested for verification purpose. In principle, the investigations are mainly driven by the efforts of minimizing the Unbalanced Magnetic Force. In this research, a reduction of Unbalanced Magnetic Force is achieved by implementing two approaches, i) non-uniform number of turns per coils in every tooth in a respective phase, and ii) an asymmetric design of stator. The investigation shows that only the first implementation technique is successful as reducing the existing Unbalanced Magnetic Force by 18% without damaging the desired torque performance in the subjected machines. Although the second implementation technique also could reduce the Unbalanced Magnetic Force, severe degradation of the torque performance as well as a bigger cogging torque existed. It is also shown that that the Unbalanced Magnetic Force is mostly influenced by it radial component instead of the tangential component. A reduction of radial force component result in a smaller Unbalanced Magnetic Force globally. Practically, the optimized design of machine is recommended for industrial applications which requires accurate position control such as robotic arm and conveying system.